Cultural Identity and Economic Resistance in Banten’s Pesantrens - Ahmad, Ikhsan; Truna, Dody S. (UIN Sunan Gunung Djati Bandung, 2025)
This study examines the resistance movement led by Kyai leaders of Salafiyah Islamic Boarding Schools (Pesantren) in Pandeglang and Serang Districts, Banten, against the establishment of PT Mayora factory in 2016. The resistance emerged in response to what was perceived as modern capitalist expansion threatening environmental sustainability and local cultural identity. Employing a qualitative approach with case study methodology, this research investigates traditional pesantren's dual role as religious educational institutions and as frontline defenders of ecological balance and cultural heritage. The study frames this resistance within political theology, analyzing how moral values derived from Islamic teachings inform opposition to capitalism's negative impacts on local communities. Data were collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that traditional pesantren serve both as religious educational institutions and as guardians of local wisdom through social-religious movements guided by the principle of Amar Ma'ruf Nahi Munkar (promoting good and preventing harm). The conflict illustrates the tension between economic interests and religious-cultural values. This study recommends strengthening traditional pesantren's role in maintaining socio-ecological sustainability within sustainable development frameworks.